2022
DOI: 10.13075/ijomeh.1896.01940
|View full text |Cite
|
Sign up to set email alerts
|

Mental well-being of healthcare workers in 2 hospital districts during the first wave of the COVID-19 pandemic in Finland: a cross-sectional study

Abstract: Objectives:The COVID-19 pandemic has caused unseen pressure on healthcare systems in many countries, jeopardizing the mental well-being of healthcare workers. The authors aimed to assess the mental well-being of Finnish healthcare workers from 2 hospital districts (Helsinki University Hospital [HUS] and Social and Health Services in Kymenlaakso [Kymsote]) with differing COVID-19 incidence rates during the first wave of the COVID-19 pandemic in spring 2020. Material and Methods: A total number of 996 healthcare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Given that infections among HCWs are associated with inadequate PPE and close contact with COVID-19 patients ( 20 , 24 , 25 ), it is understandable that PPE shortages are associated with higher levels of emotional distress ( 11 , 13 , 26 ), not to mention the fear of infecting loved ones. Our findings confirm the association between PPE shortages and perceived distress among HCWs ( 27 ).…”
Section: Discussionsupporting
confidence: 89%
“…Given that infections among HCWs are associated with inadequate PPE and close contact with COVID-19 patients ( 20 , 24 , 25 ), it is understandable that PPE shortages are associated with higher levels of emotional distress ( 11 , 13 , 26 ), not to mention the fear of infecting loved ones. Our findings confirm the association between PPE shortages and perceived distress among HCWs ( 27 ).…”
Section: Discussionsupporting
confidence: 89%
“…The pandemic was an economic challenge, resulting in dramatic financial problems for some [ 2 ], but it also burdened the capacity of the healthcare system and resources [ 4 ]. Rantanen and colleagues [ 10 ] found that these demands resulted in an experience of mental burden among healthcare workers, especially when workload was increased, there was a lack of time to recover from work, or protective COVID-19 instructions were insufficient. The new demands and changes were mentally challenging for working people [ 11 ], but also for family caregivers at home [ 12 ].…”
Section: Introductionmentioning
confidence: 99%